2004
DOI: 10.1093/nar/gkh623
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal zinc finger of the catalytic subunit of DNA polymerase   is responsible for direct interaction with the B-subunit

Abstract: DNA polymerase d (Pol d) plays a central role in eukaryotic chromosomal DNA replication, repair and recombination. In ®ssion yeast, Pol d is a tetrameric enzyme, comprising the catalytic subunit Pol3 and three smaller subunits, Cdc1, Cdc27 and Cdm1. Previous studies have demonstrated a direct interaction between Pol3 and Cdc1, the B-subunit of the complex. Here it is shown that removal of the tandem zinc ®nger modules located at the C-terminus of Pol3 by targeted proteolysis renders the Pol3 protein non-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 31 publications
2
43
1
Order By: Relevance
“…The amino acid changes in the cysteine-rich region of the CTDs of Pol ␦ and Pol ⑀ led to lethality or temperature sensitivity (29,48,49). The all-helical NTD of p70 is connected with the PDE domain by an 80-residue-long linker and has the potential for interaction with other DNA replication proteins and recruitment of Prim-Pol ␣ to the replication fork.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid changes in the cysteine-rich region of the CTDs of Pol ␦ and Pol ⑀ led to lethality or temperature sensitivity (29,48,49). The all-helical NTD of p70 is connected with the PDE domain by an 80-residue-long linker and has the potential for interaction with other DNA replication proteins and recruitment of Prim-Pol ␣ to the replication fork.…”
Section: Discussionmentioning
confidence: 99%
“…The CTDs of Pol ␣ and Pol ⑀ contain two zincbinding modules (Zn1 and Zn2), where Zn2 is involved in interactions with the B subunit (27,28). The CTDs of Pol ␦ and Pol also have two putative metal-binding modules, each containing four conservative cysteines (17,29). However, the second module is significantly different from Zn2 in the CTDs of Pol ␣ and Pol ⑀ because, instead of zinc, it coordinates a 4Fe-4S cluster (30,31).…”
mentioning
confidence: 99%
“…The zinc-finger domains have been suggested to be important for internal stability of the protein. 1 Furthermore, in the case of mouse Pola1 44 and yeast Pold 45 and Pole, 46 these domains have been shown to be required for binding of the catalytic subunits to the B subunits (Cdc1/Pold2) of the holoenzymes. [44][45][46] Accordingly, mutational analyses in budding yeast revealed that mutations within the zinc-finger domains of Pold and Pole abolish polymerase function in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, in the case of mouse Pola1 44 and yeast Pold 45 and Pole, 46 these domains have been shown to be required for binding of the catalytic subunits to the B subunits (Cdc1/Pold2) of the holoenzymes. [44][45][46] Accordingly, mutational analyses in budding yeast revealed that mutations within the zinc-finger domains of Pold and Pole abolish polymerase function in vivo. 46,47 In sum, given the importance of the domains lost in the different mutant versions of zebrafish Pold1, together with the indistinguishable phenotypic strengths of the three alleles, we suspect that they all represent pold1 null mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation in yeast demonstrated that mutations that affect the catalytic or proofreading functions of Pol δ interfere only with bulk DNA replication, not DNA repair, whereas those that leave the Pol activity intact but weaken the interaction between the catalytic subunit of Pol δ (Pol3) and its essential accessory subunit (Pol31) show defects in DNA replication and damage-induced DNA repair (5,6). Deletion of the gene encoding a nonessential Pol δ subunit in yeast, Pol32, also confers sensitivity to DNAdamaging agents and renders the cells defective for damage-induced mutagenesis, further implicating Pol δ in error-prone DNA repair (7).…”
mentioning
confidence: 99%